Protective effects of lithium against lead-induced toxicities in multiple systems of adult mouse. Issue 6 (29th September 2015) - Wang, Jiutao; Song, Lingzhen; Li, Kaikai; Yan, Runchuan; Hu, Xinde; Zhang, Wei; Yin, Yupeng; Zhao, Shanting
Graphical Abstract: Abstract: Occupational and environmental exposures to lead (Pb), one of the toxic metal pollutants, is of global concern. The present study aims to investigate the protective effects of lithium (Li) against Pb-induced damage in vivo and in vitro . For this purpose, 3-month-old mice received Li (250 mg per kg body weight, i.p.) and 2 hours later water containing Pb (20 mg per kg body weight, i.p.) for 2-weeks. Treatment of mice with Pb induced remarkable morphological damage in multiple organs, such as swelling and necrosis in the liver, kidney and spleen. Immunohistochemistry demonstrated that the number of newly generated cells and immature neurons in the hippocampus was significantly decreased in mice exposed to Pb when compared with those that received saline for control or Li. Furthermore, in mice exposed to Pb a higher percentage of newly generated cells differentiated into glial cells and fewer into neurons, and less newborn cells survived compared to those in controls and Li-treated mice. In mice exposed to Pb cognitive tests were impaired. Interestingly, pre-administration of Li markedly decreased Pb-induced pathological and neurological lesions in vivo and in vitro . Specifically, the reduction of hippocampal neurogenesis resulting from Pb exposure was prevented by administration of Li. In addition, we found that pretreatment with Li effectively prevented cognitive impairment in mice exposed to Pb. Furthermore, Li pretreatment significantly improved Pb-induced depletion in p-GSK-3β (Ser9) and microRNA-34c levels in the hippocampus. Collectively our findings point to the capacity of Li to attenuate Pb-induced damage.